Past and current Coronavirus outbreaks; Focusing on Coronavirus Disease 2019 in comparison with Severe Acute Respiratory Syndrome and Middle East Respiratory Syndrome - Najam Syed, Izna; Shamim, Nazia; Zaidi, Syed Muhammad Hussain (International Journal of Endorsing Health Science Research, 2020)
Background: Coronavirus Disease 2019 (COVID-19) is currently the most significant public health concern globally, having affected more than 22 million patients and caused an excess of 0.78 million deaths since its emergence in December 2019 in the city of Wuhan, China. There have been similar Coronavirus outbreaks in the past, namely Severe Acute Respiratory Syndrome Coronavirus-1 (SARS-CoV-1) and the Middle East Respiratory Syndrome Coronavirus (MERS-CoV). In this review article, we discussed the epidemiology, virology, clinical presentation, diagnostic approaches, and effective treatment modalities for COVID-19 in light of existing literature. Methodology: The aim of conducting this systematic review was to compare the three human coronavirus outbreaks: Severe Acute Respiratory Syndrome (SARS), Middle East Respiratory Syndrome (MERS) and Corona Virus Disease 2019 (COVID-19). Multiple search engines were used and PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) guidelines was referenced. Results: The findings suggest that COVID-19 shares substantial characteristics with both SARS and MERS, SARS being more closely related to COVID-19 in terms of epidemiological characters, particularly their viral reservoirs. SARS-CoV-1 and SARS-CoV-2 use the same receptor to gain access to the host cells, while MERS-CoV uses a different entry point. The radiological manifestations of SARS, MERS and COVID-19 are similar as well. Conclusion: The recurrent appearance of coronaviruses in the human population makes it crucial to study them in great details. Furthermore, owing to its similarity to previous coronavirus outbreaks, the lasting effects of COVID-19 on pulmonary tissue must be investigated. Moreover, at the time of writing this paper, no vaccines are available against Covid-19.